Synthesis and Physico-Chemical Studies of Newly Synthesized Terpolymers Derived from Salicyladehyde, Biuret and Trioxane - Bawankar, S.V.; Paliwal, L.J.; Kharat, R.B. (Asian Journal of Chemistry, 2012)
Resins as copolymers which from a special class of polymers are widely known for their applications. SABT terpolymer resins were synthesized by the condensation of salicylaldehyde and biuret with trioxane in the presence of hydrochloric acid as catalyst and using varied molar ratios of the starting materials. Terpolymer resin composition have been determined on the basis of their elemental analysis and the number average molecular weight of these terpolymer resin were determined by non-aqueous conductometric titration. The viscosity measurements carried out in DMF indicate normal behaviour. Spectral studies (IR, UV-visible and NMR) were carried out for structure elucidation and characterization of these terpolymers. TGA data were analysed to determine the characteristic and thermal stability of these resins. Electrical conductivity in solid state was ascertained to exhibit semiconducting character. Conclusively, ion exchange properties have been studied employing the batch equilibration method. In the light of all the physico-chemical and spectral evidences, the tentative structures have been proposed for SABT terpolymers.